Wither academic publishing - Abdul Majeed, Abu Bakar (Faculty of Pharmacy, 2025)
This study has investigated the challenges surrounding quality research publication and the need to be wary of predatory journals. By identifying key gaps and proposing targeted recommendations, it aims to support researchers, institutions, funding agencies, and policymakers in strengthening academic publishing standards, thus avoiding the withering of academic publishing.